2016
DOI: 10.1371/journal.pone.0156598
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the MicroRNA Repertoire in TLR-Ligand Challenged Bubaline PBMCs as a Model of Bacterial and Viral Infection

Abstract: In the present study, we used high-throughput sequencing, miRNA-seq, to discover and explore the expression profiles of known and novel miRNAs in TLR ligand-stimulated vis-à-vis non-stimulated (i.e. Control) peripheral blood mononuclear cells (PBMCs) isolated from blood of healthy Murrah buffaloes. Six small RNA (sRNA) libraries were multiplexed in Ion Torrent PI chip and sequenced on Ion Proton System. The reads obtained were aligned to the Bos taurus genome (UMD3.1 assembly), which is phylogenetically closes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Also, the mature and mature-star miRNA study can help detecting the most abundant change at 5`or 3`end or arm switching. Earlier, we have studied the expression of these miRNAs in TLR stimulated and non-stimulated PBMCs and recognized that some miRNAs were highly expressed while others were moderately expressed in both treatment and control groups [8]. This is the first report on experimental identification and validation of bubaline miRNAs.…”
Section: Panther Classification Of Mirna-target Gene Productsmentioning
confidence: 82%
See 1 more Smart Citation
“…Also, the mature and mature-star miRNA study can help detecting the most abundant change at 5`or 3`end or arm switching. Earlier, we have studied the expression of these miRNAs in TLR stimulated and non-stimulated PBMCs and recognized that some miRNAs were highly expressed while others were moderately expressed in both treatment and control groups [8]. This is the first report on experimental identification and validation of bubaline miRNAs.…”
Section: Panther Classification Of Mirna-target Gene Productsmentioning
confidence: 82%
“…However, reports on the empirical identification of miRNAs in livestock are limited. Available literature on RNAi-related works in the "black-gold" livestock-species Buffalo (Bubalus bubalis) is not available, except for the single research paper from our laboratory [8], where a total of 290 miRNAs were identified in bubaline-PBMCs out of which 130 were categorized as 'putative novel miRNAs'.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the abundantly expressed miRNAs include bta-miR-103, bta-miR-19b, -191 -29b, -15a, -19a, -30d, -30b-5p and members of the let family (let 7a-5p, let 7g and let 7f) in LPS-and CpG-treated and control samples, while bta-miR-21-5p was highly expressed in LPS-treated PBMCs only. 20 In our sequencing libraries, four Figure 5. Quantitative PCR was performed to verify expressions of the five miRNAs (ssc-miR-122, ssc-miR-129b, ssc-miR-152, ssc-miR-17-5p and ssc-miR-144) in RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently our lab explored the differentially expressed miRNAs in PBMCs culture, obtained from blood of Indian water buffaloes, challenged with ligands of toll like receptors viz. LPS, poly I:C, and CpG ODN to mimic the microbial infections and identified 160 mature and 130 novel miRNAs [58].…”
Section: Discussionmentioning
confidence: 99%